2013
DOI: 10.18542/ragros.v5i1.1414
|View full text |Cite
|
Sign up to set email alerts
|

USO DE Bacillus spp. NO CONTROLE DE FITOPATÓGENOS EM SEMENTES DE SOJA VARIEDADE BRS VALIOSA RR

Abstract: The seeds were microbiolized with the bacterial suspension in saline (0.85% NaCl) at a concentration of OD 540 = 0.5 AA and brought to a shaking table for 30 minutes. Seeds were plated on filter paper in experiments conducted in the laboratory with a completely randomized design with six treatments and five replications. We evaluated the incidence and reduction of pathogens in seeds. There was the assessment of healthy and infected seeds. The BRS Valiosa RR showed 48% of healthy seeds and 52% of infected seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…The result afore mentioned can be explained by the fact that seeds remained for 24 hours in the freezer, affecting B. subtilis cells. Different results were found by Angonese et al (2009), in which Bacillus genus bacteria showed great potential to be used as phytopathogenic fungi biological control agents, significantly reducing Fusarium graminearum and Stenocarpella maydis infection in maize seeds (Luz, 2001) and fungi incidence in soybean seeds (Bezerra et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
“…The result afore mentioned can be explained by the fact that seeds remained for 24 hours in the freezer, affecting B. subtilis cells. Different results were found by Angonese et al (2009), in which Bacillus genus bacteria showed great potential to be used as phytopathogenic fungi biological control agents, significantly reducing Fusarium graminearum and Stenocarpella maydis infection in maize seeds (Luz, 2001) and fungi incidence in soybean seeds (Bezerra et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
“…Para a microbiolização foi adotada a metodologia adaptada por Bezerra et al (2013), onde 50 sementes em cada replicata foram imersas em cada uma das suspensões (70 mL) durante 60 minutos. Para a testemunha, as sementes foram imersas somente em 70 mL de ADE.…”
Section: Methodsunclassified
“…(JUNGES et al, 2014). Essa técnica consiste em embeber o papel filtro com restritores hídricos que permita o adequado controle da germinação das sementes, de maneira a não afetar o desenvolvimento de fungos associados a sementes (BEZERRA et al, 2013).…”
Section: Introductionunclassified
“…Esse efeito pode ser atribuído à menor mobilização das reservas, menor síntese e atividade enzimática e mudanças na turgência celular (BEZERRA et al, 2013).…”
Section: Introductionunclassified